Perioperative concerns in Pott's spine: A review - Geetanjali Tolia Chilkoti; Nidhi Jain; Medha Mohta; Ashok K Saxena (Wolters Kluwer Medknow Publications, 2020)
Pott's disease is the most common granulomatous spine infection caused by tubercle bacilli and is a common site of osseous tuberculosis, accounting for 50-60% of cases. The delay in establishing diagnosis and management results in complications such as spinal cord compression and spinal deformity. The aim of this narrative review is to discuss the perioperative concerns in patients for spine surgery. The literature source for this review was obtained via PubMed, Medline, Google Scholar, Cochrane database of systematic reviews, and textbooks until December 2019. On the literature search, we could not retrieve any review article specifically discussing the perioperative concerns of spinal tuberculosis. Therefore, the aim of the present narrative review is to discuss the perioperative concerns of patients for spine surgery along with the specific concerns related to spinal tuberculosis.